Prevention and management of hypertensive crises in children with pheochromocytoma and paraganglioma - Bima, Chiara; Lopez, Chiara; Tuli, Gerdi; Munarin, Jessica; Arata, Stefano; Procopio, Matteo; Bollati, Martina; Maccario, Mauro; De Sanctis, Luisa; Parasiliti-Caprino, Mirko (Frontiers in Endocrinology, 2024)
Hypertensive crises in pediatric patients are rare conditions. However, determining their precise prevalence is more challenging than in adults due to the heterogeneity in the definition itself. These crises frequently occur without a prior diagnosis of hypertension and may indicate an underlying cause of secondary hypertension, including pheochromocytoma/paraganglioma (PPGL). The mechanisms of hypertensive crises in the pediatric population with PPGL are directly related to different types of catecholamine excess. Noradrenergic tumors typically present with sustained hypertension due to their predominant action on α1-adrenoceptors in the vasculature. Conversely, adrenergic tumors, through epinephrine binding to β2-adrenoceptors in addition to stimulation of α1and α2-adrenoceptors, more frequently cause paroxysmal hypertension. Furthermore, the biochemical phenotype also reflects the tumor localization and the presence of a genetic mutation.Recent evidence suggests that more than 80% of PPGL in pediatric cases have a hereditary background. PPGL susceptibility mutations are categorized into three clusters; mutations in cluster 1 are more frequently associated with a noradrenergic phenotype, whereas those in cluster 2 are associated with an adrenergic phenotype.Consequently, the treatment of hypertensive crises in pediatric patients with PPGL, reflecting the underlying pathophysiology, requires first-line therapy with alpha-blockers, potentially in combination with beta-blockers only in the case of tachyarrhythmia after adequate alpha-blockade.The route of administration for treatment depends on the context, such as intraoperative or presurgical settings, and whether it presents as a hypertensive emergency (elevated blood pressure with acute target organ damage), where intravenous administration of antihypertensive drugs is mandatory. Conversely, in cases of hypertensive urgency, if children can tolerate oral therapy, intravenous administration may initially be avoided. However, managing these cases is complex and requires careful consideration of the selection and timing of therapy administration, particularly in pediatric patients. Therefore, facing these conditions in tertiary care centers through interdisciplinary collaboration is advisable to optimize therapeutic outcomes.